ANTIDIABETIC EFFECT OF MIKANIA SCANDENS ON ALLOXAN-INDUCED RAT MODEL - Baishya, Rimashree; Adhikari, Anjan; Biswas, Sharmistha; Banerjee, Soma (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective was to study the evaluation of antidiabetic and antioxidant activity of different doses ethanolic extract of Mikania scandens leaves. Methods: The rats were divided into five groups of six animals each (non-diabetic control, diabetic control, standard drug-treated, and plant treated groups (250 and 500 mg/kg body weight)). Diabetes was induced in the healthy male Wistar rats (150â€“200 g body weight, 4â€“6 weeks old) by the administration of alloxan monohydrate (150 mg/kg, i.p.). On the 0th, 3th, 7th, 11th, and 15th days, the blood samples were analyzed for blood glucose. The antioxidant and antidiabetic parameters were evaluated by standard protocol. The liver tissue was used for histopathological assessment of liver damage. Results: The ethanolic extract of leaves of M. scandens showed a significant reduction (p<0.001) in the blood glucose levels and the antioxidant levels, with 500 mg/kg of body weight in the alloxan-induced diabetic rats as compared to the controls. Histopathological studies provided evidence that the leaf extract possesses antidiabetic activity. Conclusions: The ethanolic extract of leaves of M. scandens showed potent antidiabetic and antioxidant abilities against alloxan-induced rats, which indicate the presence of hypoglycemic constituents in the plant.